Wikipedia and libraries. Issue 1 (April 2018) - Lubbock, John
As the quality, scope and usefulness of Wikipedia (and its sister projects) increases, the Wikimedia community are increasingly reaching out to academic, library and other information professionals. Through institutional partnerships and training, we show how using Wikimedia projects can bring extra value to the library as a place of digital study and media literacy. Libraries and Wikipedia both aim to bring knowledge to a wider audience, to create spaces where people can safely learn and find the resources they need, and we believe it is possible for us to reach those goals together. This article will describe the complex and wide scope of our work with libraries and explain how our work complements the work of libraries and other cultural institutions. It will provide paths and ideas for librarians to understand how to effectively use the resources provided by Wikimedia to imagine how libraries can serve the public in our digital age.